2021
DOI: 10.1186/s13223-021-00510-z
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing enables diagnosis of X-linked hypohidrotic ectodermal dysplasia in patient with eosinophilic esophagitis and severe atopy

Abstract: X-linked hypohidrotic ectodermal dysplasia (XLHED) is the most common form of ectodermal dysplasia. Clinical and genetic heterogeneity between different ectodermal dysplasia types and evidence of incomplete penetrance and variable expressivity increase the potential for misdiagnosis. We describe a family with X-linked hypohidrotic ectodermal dysplasia (XLHED) presenting with variable expressivity of symptoms between affected siblings. In addition to the classical signs of hypohidrosis, hypotrichosis and hypodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Atopic children are at greater risk of developing FPIES [10, 12], and children with EDs have significantly more chances to present atopic diathesis and IgE-mediated allergies [2, 4, 6]. A study of 347 HED patients investigating the occurrence of digestive manifestations and food allergies showed that more than one-third of HED patients had allergic reactions to specific foods [4], but this study did not identify any cases of FPIES.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Atopic children are at greater risk of developing FPIES [10, 12], and children with EDs have significantly more chances to present atopic diathesis and IgE-mediated allergies [2, 4, 6]. A study of 347 HED patients investigating the occurrence of digestive manifestations and food allergies showed that more than one-third of HED patients had allergic reactions to specific foods [4], but this study did not identify any cases of FPIES.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is not possible to know whether FPIES in patients with EDs are related to a disturbance of the barrier functions of the skin and mucous membranes or whether they are full part symptoms of ED with a variable expression [4]. Some authors [2] suggest that manifestations of atopy may be part of the ED picture and base their argument on the absence of pathogenic variants predisposing to atopy. We also did not find any variants predisposing to atopy in the clinical exome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ectodermal dysplasia (ED) is a series of clinically and genetically heterogeneous disorders, characterised by abnormal development of the ectodermal structures, such as nails, teeth, hair, or exocrine glands [1][2][3] , and with over 200 distinct clinical phenotypes. As the most common form of ED, approximately 95% Hypohidrotic ectodermal dysplasia (HED) 4 patients have X-linked HED (XLHED), 5 and 5% have autosomal dominant and recessive HED.…”
Section: Introductionmentioning
confidence: 99%